A relação entre a natureza e o fetiche da mercadoria em Karl Marx - Jacques, Luis Fernando (2023)
The relationship between the concept of nature and the commodity fetish in Karl Marx's thought in the face of the ecological crisis promoted by capital is a complex issue that will be addressed in this paper. The aim is to examine the connection between the fetishism of religious thought and the commodity fetish and to analyze the consequences of the latter for human practice, its relationship to itself and to nature. In the era of the rule of capital over labor, social contradictions arise that profoundly change the processes of production and the metabolism between humans and nature. The question of nature in Marx, which is methodically delineated in this work, is not only a moment of materialist dialectics, but a constitutive element of the totality of the manifold determinations of the logic of value. The conceptualization of nature in this study arises from the socially determined form through use value and is grounded in the development of the exchange between humans and nature, mediated by labor. The dialectical movement of the concept of nature is analyzed in its manifold determinations in relation to the concept of the commodity fetish. The first chapter introduces Marx's concept of nature and distinguishes it from the most important earlier conceptions in the history of philosophical thought. It also looks at the relationship between humans and nature as historical subjects in the metabolic regulation of their productive activity. The second chapter examines how Feuerbach's critique of religious fetishism relates to Marx's critical reflection on the concept of the commodity fetish. The aim is to understand the consequences of this fetishism and the role of ideology in the metabolic rupture between man and nature. The third chapter deals with the philosophical foundations of the subjugation of nature by the commodity form. The fourth and final chapter problematizes contemporary ideological conceptions of nature and emphasizes the need to overcome these currents of thought that obscure the predatory logic of capital over nature. The thesis emphasizes the urgency of outlining the preconditions for a new metabolic relationship between humans and nature, an ethical relationship that aims to emancipate humans from the domination of capital, to liberate nature from subjugation by the commodity form, and to go beyond the realms of capital and commodified social forms.